The Impact of Using Type-to-Speech on Substack’s ‘Play Audio’ in Independent Listening for EFL Students - Elisa Dyah Wardani; Widya Caterine Perdhani (Universitas Islam Negeri Palopo, 2026)
This qualitative case study examines how Substack's built-in Play Audio feature, a Text-to-Speech (TTS) tool, supports independent listening development among EFL students. Although TTS technology is increasingly available on everyday digital platforms, its potential to support L2 listening development in non-educational contexts remains largely unexplored. Four purposively selected Grade X and XI students in an Indonesian secondary school participated in this study. Data on this study were collected through semi-structured interviews, systematic participant observation, and reflexive field notes, and were investigated using a qualitative descriptive approach that was supported by thematic analysis. The findings revealed four themes: improved listening comprehension, vocabulary acquisition through bimodal input, real-world contextual knowledge, and motivation for independent listening. Repeated engagement with Play Audio improved students' ability to process spoken English, supported incidental vocabulary learning, exposed learners to authentic language beyond textbook norms, and fostered intrinsic motivation for autonomous listening practice. These findings contribute towards the growing studies on informal digital learning of languages and offer practical implications for EFL teachers in Indonesian secondary schools seeking accessible and authentic alternatives to conventional listening materials.